Investigation of Different Window and Wall Materials for Solar Passive Building Design. (2016) - Kirankumar, G.; Saboor, S.; Ashok Babu, T.P.
Abstract: The energy consumption associated with the cooling of the buildings is huge. In India buildings consume about 33% of country's power production for cooling and day lighting. The building enclosures such as walls, roofs and glasses play very vital role in reducing cooling loads in the buildings. The proper combination of window glass materials and wall materials can cut down the cooling costs extensively. In the present work, five different glass materials such as clear, bronze, grey, green and blue-green glass materials were selected and four different building materials such as burnt brick, cinder concrete, dense concrete and fly ash brick either side plastered with cement plaster were selected. Total twenty building models with various combinations of window glass and wall materials were designed in licensed Design builder 4.3.0.039 version and thermal analysis was carried out in Energy plus 8.1 software package. Thermal performance of various building models in four different climatic zones such as hot and dry, temperate, warm and humid and composite were investigated. From the results of the study, it is observed that fly ash brick wall building model with grey window glass is found to be energy efficient in all Indian climatic zones from the reduced cooling load point of view among all studied combinations in East, West, North and South orientations. From the results it is observed that the fly ash brick buildings with grey glass window is observed to be the most energy efficient combination for reducing cooling loads as they gain the least heat gain in south orientation (21.51 kWh) for Ahmedabad region. The results of the study help in designing energy efficient passive buildings.